Pemuridan Relasional Bagi Kedewasaan Rohani Jemaat Gereja - Marlin, John (STT Kingdom, 2024)
Spiritual maturity is related to discipleship, one form of discipleship is relational discipleship. This research aims to describe relational discipleship and spiritual maturity. This study uses a qualitative method. The research results show that relational discipleship has a positive correlation with spiritual maturity, where the higher the implementation of relational discipleship, the higher the level of spiritual maturity..